Multi-locus variable-number tandem repeat analysis of Chinese Brucella strains isolated from 1953 to 2013 - Guo-Zhong Tian; Bu-Yun Cui; Dong-Ri Piao; Hong-Yan Zhao; Lan-Yu Li; Xi Liu; Pei Xiao; Zhong-Zhi Zhao; Li-Qing Xu; Hai Jiang; Zhen-Jun Li (Infectious Diseases of Poverty, 2017)
Abstract Background Brucellosis was a common human and livestock disease caused by Brucella strains, the category B priority pathogens by the US Center for Disease Control (CDC). Identified as a priority disease in human and livestock populations, the increasing incidence in recent years in China needs urgent control measures for this disease but the molecular background important for monitoring the epidemiology of Brucella strains at the national level is still lacking. Methods A total of 600 Brucella isolates collected during 60 years (from 1953 to 2013) in China were genotyped by multiple locus variable-number tandem repeat analysis (MLVA) and the variation degree of MLVA11 loci was calculated by the Hunter Gaston Diversity Index (HGDI) values. The charts and map were processed by Excel 2013, and cluster analysis and epidemiological distribution was performed using BioNumerics (version 5.1). Results The 600 representative Brucella isolates fell into 104 genotypes with 58 singleton genotypes by the MLVA11 assay, including B. melitensis biovars 2 and 3 (five main genotypes), B. abortus biovars 1 and 3 (two main genotypes), B. suis biovars 1 and 3 (three main genotypes), and B. canis (two main genotypes) respectively. While most B. suis biovar 1 and biovar 3 were respectively found in northern provinces and southern provinces, B. melitensis and B. abortus strains were dominant in China. Canine Brucellosis was only found in animals without any human cases reported. Eight Brucellosis epidemic peaks emerged during the 60 years between 1953 and 2013: 1955 – 1959, 1962 – 1969, 1971 – 1975, 1977 – 1983, 1985 – 1989, 1992 – 1997, 2000 – 2008 and 2010 – 2013 in China. Conclusions Brucellosis has its unique molecular epidemiological patterns with specific spatial and temporal distribution according to MLVA. Trial registration IDOP-D-16-00101.